2015
DOI: 10.1063/1.4929721
|View full text |Cite
|
Sign up to set email alerts
|

Kink and kink-like waves in pre-stretched Mooney-Rivlin viscoelastic rods

Abstract: The present paper theoretically investigates kink and kink-like waves propagating in pre-stretched Mooney-Rivlin viscoelastic rods. In the constitutive modeling, the Cauchy stress tensor is assumed to consist of an elastic part and a dissipative part. The asymptotic method is adopted to simplify the nonlinear dynamic equations in the limit of finite-small amplitude and long wavelength. Using the reductive perturbation method, we further derive the well-known far-field equation (i.e. the KdV-Burgers equation), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Hence it is not appropriate to describe the dissipative stress in the solid usingĖ left . Recent studies [24,30] have also emphasized that the strain-rate tensor is not appropriate for incorporating viscous dissipative effects, as it yields unphysical results in the context of wave formation in prestressed viscoelastic solids [31]. In this work, we employ both formulations and demonstrate how the use of the (incorrect) strain-rate formulation for the dissipative stress leads to results that are drastically different from the rate-of-deformation formulation.…”
Section: Problem Formulationmentioning
confidence: 96%
“…Hence it is not appropriate to describe the dissipative stress in the solid usingĖ left . Recent studies [24,30] have also emphasized that the strain-rate tensor is not appropriate for incorporating viscous dissipative effects, as it yields unphysical results in the context of wave formation in prestressed viscoelastic solids [31]. In this work, we employ both formulations and demonstrate how the use of the (incorrect) strain-rate formulation for the dissipative stress leads to results that are drastically different from the rate-of-deformation formulation.…”
Section: Problem Formulationmentioning
confidence: 96%
“…Moreover, the excitations of different nonlinear waves can be tuned by changing the axial pre-stretch. Furthermore, the kink and kink-like waves propagating in pre-stretched Mooney-Rivlin viscoelastic rods were investigated by Wang et al [105]. The numerical examples indicated that the pre-stretch and viscosity influence the wave shape and nonlinear wave velocity.…”
Section: Nonlinear Wavesmentioning
confidence: 99%
“…Inspired by the earlier works mentioned above, we have conducted a systematic investigation in recent years on wave propagation in soft materials and structures in various configurations [17,18,[37][38][39][40][41][42]. In this paper, we intend to show that the combination of large deformation and electromechanical coupling can lead to a very flexible and efficient way to tune the BGs by considering a simple phononic cylinder of soft electroactive elastomer with periodic electric boundary conditions.…”
Section: Introductionmentioning
confidence: 99%